Acetato(aqua){6,6′-dimethoxy-2,2′-[ethane-1,2-diylbis(nitrilomethanylylidene)]diphenolato}cobalt(III) methanol disolvate - Gervas Assey; Ray J. Butcher; Yilma Gultneh (Acta Crystallographica Section E, 2012)
In the title complex, [Co(C18H18N2O4)(C2H3O2)(H2O)]·2CH3OH, the CoIII atom is hexacoordinated by water and acetate groups in the axial positions and by the tetradentate Schiff base occupying equatorial positions. These axial bonds are longer than the equatorial bonds to the tetradentate Schiff base. Two molecules form a dimer through strong hydrogen bonds from the coordinated water of one molecule to the methoxy O atoms of an adjoining molecule. There is extensive intra- and intermolecular O—H...O hydrogen bonding between the coordinated water and acetate ligands and the methanol solvent molecules. In addition, there are weak intermolecular C—H...O interactions, which link the molecules into a three-dimensional array.